Geomechanical modelling of Paleozoic Shale Gas Formation: a case study from the Baltic Basin, northern Poland - Słota-Valim, Małgorzata; Sowiżdżał, Krzysztof; Jędrzejowska-Tyczkowska, Halina (Geology, Geophysics and Environment, 2018)
The article presents the importance and position of geomechanical modelling workflow in reservoir characterization studies dedicated to unconventional shale reservoirs. We show the results of 3D geomechanical modelling carried out in an onshore area within the Baltic Basin, northern Poland, where the Silurian and Ordovicianshale formations are the exploration targets. The fundamental elements of the methodology, processes, and available datasets used in the modelling are discussed. The petrophysical, elastic, and mechanic properties of the rock were applied in the modelling process, along with the principal stresses and pore pressure in the geological formation. Moreover, the main calculation methods and data requirements for the Mechanical Earth Model construction are discussed. A comprehensive 3D geomechanical model was constructed, providing important information to engineers and decision makers which allows them to optimize well placement, the direction of the horizontal section of the borehole and the parameters of hydraulic fracturing treatment. The model can identifyzones of higher potential within the area of interest in terms of efficient stimulation treatment design.